2002
DOI: 10.1097/00001813-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of high-dose etoposide in children receiving different conditioning regimens

Abstract: Pharmacokinetics after high-dose (HD) etoposide (Eto) (40 mg/kg i.v. once as 4-h infusion, one patient 20 mg/kg i.v. as 4-h infusion, for 3 consecutive days) were studied in 31 children and young adults (age 0.8-23.7 years, median: 8.0 years) undergoing bone marrow transplantation after different conditioning regimens. Blood samples were collected until 97 h after the end of infusion. The population analysis of the first part of data (112 samples/21 patients, well documented) served to establish the pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
10
1
Order By: Relevance
“…For high-dose cyclophosphamide treatment (1,850-7,000 mg/m 2 ), the maximum reported serum concentration (Cmax) was 2.664 mg/mL [24,25]. For high-dose etoposide treatment (1,480-1,665 mg/m 2 ), the reported Cmax was 0.1 mg/mL [26,27]. Based on this information, the CC10 was selected as the drug concentration for further experiments.…”
Section: Etoposide Increases Il-8 Secretion From Bmscs and Causes Lonmentioning
confidence: 99%
“…For high-dose cyclophosphamide treatment (1,850-7,000 mg/m 2 ), the maximum reported serum concentration (Cmax) was 2.664 mg/mL [24,25]. For high-dose etoposide treatment (1,480-1,665 mg/m 2 ), the reported Cmax was 0.1 mg/mL [26,27]. Based on this information, the CC10 was selected as the drug concentration for further experiments.…”
Section: Etoposide Increases Il-8 Secretion From Bmscs and Causes Lonmentioning
confidence: 99%
“…There are many studies describing VP‐16 PK, although there are still only a few concerning children who underwent HSCT and received high‐dose VP‐16 as a conditioning regimen (9, 10). Concurrently, there is no study referring to children with ALL conditioned with FTBI and VP‐16 at a single dose of 60 mg/kg, which nowadays is one of the major regimens used in children with ALL, the most common indication for allo‐HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…A clearance of etoposide at a range lower than that reported in the literature was described in children who underwent treatment with high-dose etoposide. 20 As regard actinomycin D, a study performed in a pediatric population reported a higher median exposure in children whose body weight was <40 kg. 21 A possible role of age in the pharmacokinetics of doxorubicin is not well defined.…”
Section: Discussionmentioning
confidence: 99%